SAT0066 Histological and ultrasound synovial predictors of clinical differentiation to defined arthritis in patients with seronegative undifferentiated peripheral inflammatory arthritis. (15th June 2017) - Alivernini, S; Petricca, L; Tolusso, B; Bui, L; Mario, C Di; Gigante, MR; Sante, G Di; Benvenuto, R; Fedele, AL; Federico, F; Gremese, E; Ferraccioli, G
Abstract : Background: Undifferentiated Peripheral Inflammatory Arthritis (UPIA) is a common diagnosis at the first clinical evaluation in rheumatological settings. However, the likelihood of developing a well-defined rheumatic disease in UPIA patients is still matter of debate. Objectives: To examine the role of ultrasound (US) and histological parameters in the disease outcome of patients with seronegative UPIA. Methods: Fourty-two patients with IgA/IgM-Rheumatoid Factor and anti-citrullinated peptide antibodies negative UPIA, naïve to any Disease-Modifying Anti-Rheumatic Drugs, underwent Gray Scale (GSUS) and power Doppler (PDUS) evaluation and US guided synovial tissue biopsy. Synovial expression of CD68, CD3, CD21, CD20 and CD31 was evaluated by immunohistochemistry. IL-6, VEGF-A and VEGF-D peripheral blood (PB) and synovial fluid (SF) levels were measured by ELISA. To exclude Reactive Arthritis, each patient underwent genital and throat swabs. Afterwards, each UPIA patient was treated with chloroquine 250 mg/daily and followed every 3 months for 1 year and classified as having UPIA, Rheumatoid Arthritis (RA), Spondyloarthritis (SpA) or Psoriatic Arthritis (PsA), respectively. Results: During the follow-up 6 (14.3%) UPIA reached a defined diagnosis (2 RA, 2 SpA and 2 PsA, respectively). At baseline, UPIA who differentiated had higher GSUS (p=0.01) and PDUS scores (p=0.02) compared to patients who remained as UPIA within 1 year. At baseline, UPIA who differentiated towards defined arthritis had higher histological scores for lining and sublining CD68 + (p=0.005 and p=0.04 for lining and sublining, respectively), sublining CD3 + cells (p=0.002) and CD31 + vessels count (p<0.001) than patients who remained as UPIA. In addition, there were direct correlations between baseline GSUS and PDUS scores with lining CD68 + cells scores (p<0.001 for GSUS and p=0.02 for PDUS scores respectively), sublining CD68 + cells scores (p=0.02 for GSUS and p=0.03 for PDUS scores respectively), sublining CD3 + cells score (p=0.002 for GSUS and p=0.002 for PDUS scores respectively) and CD31 + vessels count (p<0.001 for GSUS and p=0.01 for PDUS scores respectively) in UPIA. Finally, the areas under the receiver operating characteristic (ROC) curves CD31 + vessels count (cut-off value: 24.3), GS score (cut-off value: 1.5) and PDUS score (cut-off value: 1.5) were calculated to assess the best cut-off points to identify the differentiation likelihood during the follow-up in UPIA patients. The logistic regression analysis, demonstrated that having baseline GSUS and PDUS scores ≥1.5 [OR:13.64 (95% CI: 0.98–242.59); p=0.05] and CD31 + vessels count ≥24.3 [OR:51.13 (95% CI: 3.15–829.16); p=0.01] were independent factors associated with the achievement of defined arthritis. Conclusions: Histological and US assessment may help in the identification of patients with seronegative UPIA with high likelihood of clinical differentiation towards defined arthritis. Disclosure of Interest: None declared